Mobile banking acceptance model for Generation Z: The role of trust, self-efficacy, and enjoyment - Fitriati, Azmi; Tubastuvi, Naelati; Mudjiyanti, Rina; Wahyuni, Sri; Ibarra, Venus C. (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This research aims to develop a model that explains m-banking acceptance behavior, especially for Generation Z, which is driven by perceptions of trust, self-efficacy, and enjoyment.Design/Methodology/Approach: The population was Generation Z as users of m-banking in Indonesia. The data collection instrument employed a questionnaire. The analysis technique used was component or variance-based Structural Equation Modeling (SEM) utilizing Partial Least Square (PLS)Research findings: The results showcased that trust, self-efficacy, and enjoyment influenced perceived usefulness and ease of use. These perceptions influenced attitudes, intentions to use, and use of m-banking. Generation Z m-banking users believe that potential risks could be resolved effectively and efficiently. They have high confidence that they will be able to overcome problems.Theoretical contribution/Originality: This research has succeeded in developing TAM by adding trust, self-efficacy, and enjoyment. Generation Z users prioritize not only ease of use but also the usability and advantages of application services. Those who have self-confidence will choose services that offer security and comfort. Applications that receive a positive response from their users will encourage their use.Research limitation/Implication: The results of previous research still contain gaps regarding the role of research variables. Therefore, it is necessary to study in more depth the m-banking acceptance model of Generation Z.